2019
DOI: 10.3390/nu11020384
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acids’ Level and Nutrition in Critically Ill Patients and Association with Outcomes: A Prospective Sub-Study of PermiT Trial

Abstract: Objectives: The objectives of this study were to evaluate the clinical and nutritional correlates of high free fatty acids (FFAs) level in critically ill patients and the association with outcomes, and to study the effect of short-term caloric restriction (permissive underfeeding) on FFAs level during critical illness. Patients/Method: In this pre-planned sub-study of the PermiT (Permissive Underfeeding vs. Target Enteral Feeding in Adult Critically Ill Patients) trial, we included critically ill patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
9
0
3
Order By: Relevance
“…Biologically, FFA mainly originates from the hydrolysis of TG and serves as a preferred energy fuel for tissue (29). Acute critical illnesses, such as trauma or sepsis, could induce elevated FFA levels in serum (30). In cerebral diseases, FFA has been proven to be independently associated with both the poor prognosis and stroke recurrence in patients with ischemic stroke (31,32); however, scarce data reveal the roles of serum FFA in aSAH outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Biologically, FFA mainly originates from the hydrolysis of TG and serves as a preferred energy fuel for tissue (29). Acute critical illnesses, such as trauma or sepsis, could induce elevated FFA levels in serum (30). In cerebral diseases, FFA has been proven to be independently associated with both the poor prognosis and stroke recurrence in patients with ischemic stroke (31,32); however, scarce data reveal the roles of serum FFA in aSAH outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological reference range for plasma FFA concentrations in our laboratory ranged from 0.100 to 0.600 mmol•L −1 . In the ICU patients, Arabi et al [7] considered a cut-off value to be 0.45 mmol•L-1 in females and 0.6 mmol•L −1 in males, as the upper limits of normal. In accordance with their cut off, 29.1% of the patients had elevated levels of FFAs at the start of the study, which was almost the same as the Arabi study (32.8%).…”
Section: Plasma Total Ffa and Individual Famentioning
confidence: 99%
“…The provision of specific types of TPN admixtures for several weeks significantly changed the concentrations of total FFAs in plasma. From a clinical point of view, it has been reported that high concentrations of FFA are present in patients with acute respiratory distress syndrome or sepsis [7,37]. Thus, FFA modulation may be important in positively influencing the inflammatory markers; however, the exact mechanism is unclear.…”
Section: Plasma Total Ffa and Individual Famentioning
confidence: 99%
See 1 more Smart Citation
“…Early critical illness is associated with impaired β‐oxidation and reduced enzyme concentrations and thus an inability to effectively utilize fat 3,19 . This is associated with decreased mitochondrial biogenesis and a compromised bioenergetic status 19,26 …”
Section: Effect Of Critical Illness On Mitochondrial Functionmentioning
confidence: 99%